2022
DOI: 10.1002/cpz1.378
|View full text |Cite
|
Sign up to set email alerts
|

Identification of B Cell and T Cell Epitopes Using Synthetic Peptide Combinatorial Libraries

Abstract: This unit presents a combinatorial library method that consists of the synthesis and screening of mixture-based synthetic combinatorial libraries of peptide molecules. The protocols employ peptide libraries to identify peptides recognized by mAbs and T cells. The first protocol uses a positional scanning peptide library made up of hexapeptides to identify antigenic determinants recognized by mAbs. The 120 mixtures in the hexapeptide library are tested for their inhibitory activity in a competitive ELISA. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Synthetic combinatorial peptide libraries have been used successfully to identify bioactive peptides, including antimicrobial peptides [42], opioid receptor antagonists [43], ligands for cell surface receptors [44], and T cell epitopes [45]. Here, we demonstrated that the brain tumor EV-specific peptides can be used to inhibit EV-induced neuronal cytotoxicity in a dose-dependent manner, suggesting that these peptides can be exploited as novel inhibitors for preventing tumor pathogenesis.…”
Section: Discussionmentioning
confidence: 83%
“…Synthetic combinatorial peptide libraries have been used successfully to identify bioactive peptides, including antimicrobial peptides [42], opioid receptor antagonists [43], ligands for cell surface receptors [44], and T cell epitopes [45]. Here, we demonstrated that the brain tumor EV-specific peptides can be used to inhibit EV-induced neuronal cytotoxicity in a dose-dependent manner, suggesting that these peptides can be exploited as novel inhibitors for preventing tumor pathogenesis.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, upon inspection of TCR gene usage in murine models of MASH, we observed very little overlap between individual mice (Supplemental Figure 6), suggesting that multiple antigenic targets may cause the T cell activation and accumulation in the liver during MASH. Thus, the antigenic cause(s) of T cell activation in MASH remains unclear and future studies require high-throughput, unbiased approaches 52 to determine the repertoire of stimulatory antigens in MASH. While elucidating the antigenic causes of clonal expansion in MASH will likely be time consuming, this discovery could clarify the role and function of CD8 + T cells in MASH pathogenesis and lead to future targeted MASH treatments, focusing on CD8 + T cell function.…”
Section: Discussionmentioning
confidence: 99%